Respiratory complications from acute corrosive poisonings in adults - Chibishev, Andon A; Natasa Simonovska; Bozinovska, Cvetanka; Zanina Pereska; Smokovski, Ivica; Glasnovic, Marija (Academy of Medical Sciences of Bosnia and Herzegovina, 2014)
Acute corrosive poisonings are caused by ingestion of corrosive chemicals which are most commonly used as household agents. Intoxications with these kind of agents produce numerous and severe post-corrosive complications of the upper gastrointestinal tract. On the other hand, our experience showed that corrosive agents may also cause injuries of the respiratory system, which makes the treatment very hard and additionally complicates the severe clinical condition of the patient.
Keywords: corrosive poisonings; systemic complications; pneumonia; post-corrosive complications